2014
DOI: 10.1126/science.1250255
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitylome analysis identifies dysregulation of effector substrates in SPOP-mutant prostate cancer

Abstract: Cancer genome characterization has revealed driver mutations in genes that govern ubiquitylation; however, the mechanisms by which these alterations promote tumorigenesis remain incompletely characterized. Here, we analyzed changes in the ubiquitin landscape induced by prostate cancer-associated mutations of SPOP, an E3 ubiquitin ligase substrate binding protein. SPOP mutants impaired ubiquitylation of a subset of proteins in a dominant-negative fashion. Of these, DEK and TRIM24 emerged as effector substrates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
226
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(244 citation statements)
references
References 38 publications
18
226
0
Order By: Relevance
“…Crystal structures of subsets of CRL complexes and SPOP can be used to build a model of CRL3 SPOP without additional assumptions (Movie EV2). The model suggests that cullin/Rbx1 binding to each SPOP monomer is not impeded by SPOP oligomerization, which is in agreement with experimental data (Theurillat et al , 2014). The helical propensity of the SPOP oligomer places the cullin molecules in a spiral arrangement, with each arm bent toward the helical axis (van Geersdaele et al , 2013).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Crystal structures of subsets of CRL complexes and SPOP can be used to build a model of CRL3 SPOP without additional assumptions (Movie EV2). The model suggests that cullin/Rbx1 binding to each SPOP monomer is not impeded by SPOP oligomerization, which is in agreement with experimental data (Theurillat et al , 2014). The helical propensity of the SPOP oligomer places the cullin molecules in a spiral arrangement, with each arm bent toward the helical axis (van Geersdaele et al , 2013).…”
Section: Resultssupporting
confidence: 89%
“…Truncated SPOP constructs encoding the BTB and BACK domains self‐associate into higher‐order oligomers (Errington et al , 2012) that possess increased ubiquitination efficiency, supporting the functional importance of oligomerization (Zhuang et al , 2009; Errington et al , 2012). Mutations within the MATH domain perturb interactions with substrates (Geng et al , 2013, 2014; Theurillat et al , 2014; Zeng et al , 2014; Zhang et al , 2015). Mutations within both self‐association domains are also found in cancers [Appendix Fig S1 and www.cbioportal.org (Cerami et al , 2012; Gao et al , 2013)], further supporting a functional role for higher‐order oligomerization, but their pathological mechanism is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…S6B). Theurillat et al recently analyzed the protein levels of a novel SPOP substrate, DEK, in prostate tumor cell lines, where different SPOP variants were overexpressed (36). Consistent with our findings, they observed that DEK levels were significantly elevated in the case of missense variants in the substrate-binding pocket (cluster S) but not in the case of SPOP-E50K (which falls in our cluster E).…”
Section: Significancesupporting
confidence: 90%
“…Intriguingly, functional annotation analysis revealed among the 323 putative targets a striking prevalence of genes involved in protein ubiquitination and specifically encoding components of the E3 ubiquitin ligase complexes (n = 29) ( Figure 5B and Supplemental Table 2). Proteins of the E3 ubiquitin ligase complex are emerging as important oncogenic or tumor suppressor factors deregulated as a consequence of genetic events in various cancers, including prostate cancer (16,18,19). Notably, among the top miR-424 targets we found the E3 ubiquitin ligase COP1 (also known as RFWD2), which is a known tumor suppressor deleted in 3%-8% of prostate cancers and other types of tumors (16,19).…”
Section: Mir-424 Is Upregulated In Prostate Tumors and Associated Witmentioning
confidence: 94%
“…Deregulated expression of miRNAs is very frequent in human cancers, including prostate cancer (13)(14)(15). Mutations and deletions of genes encoding components of the ubiquitin ligase complexes resulting in altered protein ubiquitination and turnover are also emerging as important mechanisms driving prostate tumorigenesis (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%